Explaining Voter Loyalty in Indonesia's Regional Representative Election: The Case of Cerint Iralloza Tasya in West Sumatra - Diffa Khoirunnisa (Journal of Social and Policy Issues, 2026)
The 2024 General Election and the subsequent Re-vote (PSU) in West Sumatra present an intriguing case study in voter behavior dynamics, featuring a young female candidate and recent graduate—Cerint Iralloza Tasya—who secured the highest number of votes in the 2024 West Sumatra Regional Representative Council (DPD) election. This study aims to describe the consistency of voter behavior among Cerint’s supporters during the 2024 DPD RI election in West Sumatra. It employs a qualitative approach utilizing a case study method, grounded in the voter behavior theory proposed by Adman Nursal. Psychological factors played a significant role; the initial election victory created a perception of her as a "leading candidate," thereby encouraging voters to maintain their support during the Re-vote (PSU). Furthermore, Cerint’s platform addressed issues that resonated deeply with the public, while her campaign methods and extensive use of social media were key drivers in voters' decisions to support her in the 2024 West Sumatra DPD RI election. These findings reinforce psychological theories regarding voter behavior, specifically the concept of cognitive consistency, demonstrating that consistent voting patterns are shaped by psychological factors. Cerint successfully cultivated these elements, enabling her to sustain consistent voter support across both the initial election and the Re-vote for the DPD RI in West Sumatra.